Pembagian Harta Warisan Berdasarkan Perspektif Hukum Perdata dan Hukum Islam - Dika Ratu Marfu’atun; Asep Dharmawan; Natasha Apriliani; Sofia Billa Paradise (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Inheritance law regulates a person's wealth after the owner dies. In general, the system of inheritance or distribution of wealth can be done in three ways: using BW law (Burgerlijk Wetboek), Islamic law, and customary law. This research method uses a qualitative research method with a normative juridical research type with an observational approach which is intended to examine legal issues related to the comparison of the distribution of inheritance assets according to Civil Law and Islamic Law. The aim of this research is to find out how inheritance is divided according to western civil law and Islamic lawAccording to civil law, there are two ways to divide inherited assets, namely Ab-intestato (heirs according to law article 832 of the Civil Code) and Testamentair (Will). Meanwhile, in Islamic law, men get two parts, while women get one part (2:1). When a man marries, the inheritance he receives from his parents will be used to pay the dowry and support his wife and children.